Comparison between two target functions for optimization of single phase shaded-pole motor using method of genetic algorithms - Sarac, Vasilija; Petkovska, Lidija; Cundev, Milan; Cvetkovski, Goga (Elsevier BV, 2005)
Method of genetic algorithms (GAs) has been started to be widely used, as an optimization technique of electrical machines, in the recent years. In this paper the GA method will be applied on the shaded-pole motor, aiming towards an improvement of its operational and performance characteristics. The authors develop two new improved motor models, starting from the basic one. In the first motor model the electromagnetic torque, as a target function for optimization is suggested, while in the second one the optimization is based on the efficiency factor, used as a target function. The results gained from the both motor models are analyzed and compared to the basic model. The conclusions regarding the more favorable target function for optimization of a single phase shaded-pole motor are presented.
Keywords: genetic algorithm, shaded pole induction motor, optimization